Associations of Antidepressants With Atrial Fibrillation and Ventricular Arrhythmias: A Systematic Review and Meta-Analysis - Cao, Yalin; Zhou, Mingyu; Guo, Huaiyun; Zhu, Wengen (Frontiers in Cardiovascular Medicine, 2022)
Background: Several published studies have disagreements on whether the use of antidepressants is associated with increased risks of arrhythmias. Herein, we performed this meta-analysis to assess the association of antidepressants with cardiac arrhythmias in patients who requires antidepressants. Methods: The PubMed and Embase databases were systematically searched until December 2021 to find studies that investigated the association between antidepressant use and cardiac arrhythmias. Studies that assessed the effects of any antidepressant on arrhythmias in patients who require antidepressants compared with no antidepressants were included. We used a random-effects model to pool the adjusted risk ratios (RRs) and 95% confidence intervals (CIs). The stability of the results was examined by omitting an individual study at a time. Results: A total of 7091 studies were screened and 6 studies with 2626746 participants were finally included in this meta-analysis. When compared with no antidepressants, the use of antidepressants was significantly associated with an increased risk of atrial fibrillation (RR=1.37, 95%CI: 1.16-1.61). However, there was no difference in the risk of ventricular arrhythmias or sudden cardiac death (RR=1.33, 95%CI: 0.88-2.01) between the two studied groups. In the subgroup analysis, tricyclic antidepressants (RR=1.12, 95%CI: 0.89-1.41), selective serotonin reuptake inhibitors (RR=1.46, 95%CI: 0.63-3.38), and selective serotonin reuptake inhibitors (RR=0.99, 95%CI: 0.97-1.01) did not increase the risk of ventricular arrhythmias and/or sudden cardiac death. Conclusions: Current published data suggested that the use of antidepressants did not increase the risk of ventricular arrhythmias or sudden cardiac death. Antidepressants were associated with an increased risk of atrial fibrillation but still need further confirmation.